The Effect of Principal Leadership and School Climate on the Teacher Performance at SMP Negeri in the Tarantang Sayang Region, Tanah Datar District - Eva Yanti; Syahril; Hadiyanto; Nellitawati (CV. AFDIFAL MAJU BERKAH, 2022)
This research background from the results of the author's observations regarding the influence of the principal's leadership and school climate on teacher performance at SMP Negeri in the Tarantang Sayang Region, Tanah Datar Regency which shows that the principal's leadership and school climate are still not good and teacher performance is still low. This research aims toobtain data and information about (1) the positive influence of the principal's leadership on teacher performance at SMP Negeri in the Tarantang Sayang Region, Tanah Datar Regency, (2) The positive influence of school climate on teacher performance at SMP Negeri in the Tarantang Sayang Region, Tanah Datar Regency, and (3) the positive influence of the principal's leadership and school climate on teacher performance at SMP Negeri in the Tarantang Sayang Region, Tanah Datar Regency.This type of research is quantitative correlationalwith associative type. The population of this study namelyPNS teachers totaling 120 teachers, with a research sample of 68 teachers taken by techniqueproportionate stratified random sampling. Data analysis usingmultiple linear regression test processed using SPSS version 24. The research results showthat there is a significant influence between the principal's leadership on teacher performance with tcount>ttable (2.118>1.997). There is a significant influence between school climate and teacher performance with tcount>ttable (2.226>1.997). There is a significant influence between the principal's leadership and school climate on teacher performance with a value of Fcount>Ftable (6.858> 3.14), so there is a significant influence between the principal's leadership and school climate together on teacher performance.